Eddies in the Tropical Atlantic Ocean and Their Seasonal Variability. Issue 21 (5th November 2019) - Aguedjou, H. M. A.; Dadou, I.; Chaigneau, A.; Morel, Y.; Alory, G.
Abstract: We study mesoscale eddy characteristics in the tropical Atlantic Ocean, using 23 years of daily altimetry sea level anomalies. Eddies are mainly generated in the eastern boundary upwelling systems and in the Brazil Current region. Their westward propagation speed reaches 20 cm/s in equatorial areas, decreasing with latitudes. They present typical amplitudes of 1‐5 cm. The largest and most energetic eddies are observed in the equatorial region, especially in the North Brazil Current (NBC) retroflection. The seasonal cycle of the eddy characteristics shows higher amplitudes along the NBC retroflection and the western part of the North Equatorial Countercurrent. A new criterion, based on altimetry data, determines the probability that barotropic instability of mean surface currents is responsible for eddy generation. We find a strong likelihood that the latter plays a key role along the North Equatorial Countercurrent, whereas other mechanisms must be invoked for the NBC region. Key Points: Mesoscale eddies in the tropical Atlantic ocean have amplitudes, radii, and kinetic energies of 1–5 cm, 30–100 km, and 50–100 cm 2 /s 2, respectively Seasonal cycle of eddy properties has the highest amplitude in the NBC retroflection and in the western part of the NECC Barotropic instability is the main mechanism for eddy generation in the western part of the NECC Plain Language Summary: The kinetic energy in the ocean is dominated by mesoscale eddies that are quasi‐circular structures having typical spatial scales of 10 to 100 km. Eddies have a clear signature in sea surface height measured by satellite altimeters and play a significant role in the transport and redistribution of water masses, heat, and biogeochemical properties throughout the oceans. In this work, we use 23 years of satellite altimetry data in the tropical Atlantic Ocean to analyze eddy properties (size, amplitude, kinetic energy, and vorticity) at the basin scale and their seasonal variability. Although they are more numerous on the borders of the subtropical gyres, the most energetic and largest eddies are found in the equatorial region. Eddy characteristics exhibit the strongest seasonal cycle in the North Brazil Current retroflection and the western part of the North Equatorial Countercurrent. In this latter region, eddy genesis is due to barotropic instabilities resulting from the horizontal shear of the large‐scale currents, whereas in the North Brazil Current retroflection other processes have to be considered.